Antioxidant Activity of Bioactive Compounds in the Ethyl Acetate Extract of Putat Leaves (Planchonia valida) - Nelson; Silaban, Desy Vania; Farid, Faizar; Puspitasari, Ratih Dyah; Tarigan, Indra Lasmana; Ramadhan, Ilham Ifandi; Latief, Madyawati (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2022)
The Putat leaf (Planchonia valida) is a plant traditionally used by the community in the Tanjung Lanjut area, Jambi, both as a salad ingredient and as a traditional medicine to treat skin diseases and promote health. This identifies that the putat plant contains chemical compounds that potentially have antioxidant activity. In this study, putat leaf samples (Planchonia valida) that potentially have antioxidant activity. In this study, Planchonia valida (P. valida) leaf samples using n-hexane and ethyl acetate solvents through a multistep maceration process. Subsequently, phytochemical screening and antioxidant activity tests were conducted to obtain information about fractions that have the potential to be further isolated. The extraction percentage with a yield value of 1,28% was obtained in the maceration process. Further isolation was carried out using isolate liquid chromatography and FT-IR instruments. The obtained isolate was in the form of a wet solid, and through characterization, it was classified as a steroid compound suspected to be ergosterol. Free radicals or oxidants have reactive effects on the human body and can trigger various types of diseases. Antioxidants are known to have the ability to inhibit or neutralize free radicals in the human body. This study tested antioxidant activity using the DPPH (1,1-diphenyl-1,1-picrylhydrazyl) method on isolating F1. Isolate F1 was found to have antioxidant activity with a value of 714.637 ppm, falling into the range of weak antioxidant activity